2021
DOI: 10.48550/arxiv.2106.04011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

JANUS: Parallel Tempered Genetic Algorithm Guided by Deep Neural Networks for Inverse Molecular Design

AkshatKumar Nigam,
Robert Pollice,
Alan Aspuru-Guzik

Abstract: Inverse molecular design, i.e., designing molecules with specific target properties, can be posed as an optimization problem. High-dimensional optimization tasks in the natural sciences are commonly tackled via population-based metaheuristic optimization algorithms such as evolutionary algorithms. However, expensive property evaluation, which is often required, can limit the widespread use of such approaches as the associated cost can become prohibitive. Herein, we present JANUS, a genetic algorithm that is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…GA-based generative models showed good performance in previous studies, but required large searching time [27,26]. In our experiment, we showed that MCTS is helpful to reduce the search time, and ST and GA contribute to increasing the reward and both drug-likeness and uniqueness, respectively.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…GA-based generative models showed good performance in previous studies, but required large searching time [27,26]. In our experiment, we showed that MCTS is helpful to reduce the search time, and ST and GA contribute to increasing the reward and both drug-likeness and uniqueness, respectively.…”
Section: Discussionmentioning
confidence: 51%
“…7. JANUS-C [27] was compared, which uses SELFIES [51], a trainable classifier, and GA, but not a deep generative model. Although [51] does not use a deep generative model, they train a DNN-based classifier during iterations, which is designed to distinguish high potential molecules for achieving a high reward.…”
Section: Chemts [22] Consists Of Mcts and Anmentioning
confidence: 99%
See 3 more Smart Citations